IMPROVING STUDENTS’ WRITING SKILL OF NARRATIVE TEXT THROUGH PROJECT BASED LEARNING (PJBL) AT SMKN 8 SURABAYA: English - Fanisa Rifda; Bekti Wirawati; Nunik Deniati (Journal of English Development, 2023)
Writing is a crucial skill. It provides a potent means of self-expression and encouragement for continued education and development. The study's goals were to improve student's writing skills through Project Based Learning (PJBL) and to know how Project Based Learning (PJBL) can improve students' writing skills. The research methodology employed is Classroom Action Research (CAR). This study focuses on selecting the tenth-grade Culinary 4 class at SMKN 8 Surabaya for the academic year 2022/2023, consisting of 32 students (4 males and 28 females). Each cycle consists of four discrete phases: planning, acting, observing, and reflecting. The assessment procedure consisted of two distinct components, the test, and observation. The conclusion was that Project-Based Learning (PJBL) could assist students in writing narrative texts more effectively. The improvement was reflected in the increase in the mean writing score of the students, which increased from 59.65 or 9.09%  to 69.31 or 36% in the first cycle to 79.73 or 36%. The classroom environment fosters a positive learning environment during the teaching and learning process. It encourages students to be creative in generating ideas, creating narrative text accurately using Canva technology, improving The four components of 21st-century skills, and enhancing their writing skills.